ADOPTION OF ISLAMIC BANKING IN FINANCIAL SATISFACTION : STUDY ON BANK SYARIAH INDONESIA YOGYAKARTA REGION - Heru Kristanto HC (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2022)
The main purpose of this study was to examine the effect of Islamic financial literacy, religiosity, bankreputation, and risk attitude on the adoption of Islamic banking. Examine the mediating role of the adoption ofIslamic banking on the influence of Islamic financial literacy, religiosity, bank reputation, and risk attitude onfinancial satisfaction. The statistical analysis model used mediation regression. The research population was1.033.264 and the sample was 336 Bank Syariah Indonesia customers in the Jogjakarta region. The samplingtechnique used was random sampling, a data collection method using a questionnaire. The mediationregression analysis tool uses SEM-PLS. The results show that: Islamic financial literacy has a positive effecton the adoption of Islamic banking products. Bank reputation has a positive effect on the adoption of Islamicbanking. Religiosity has a positive effect adoption of Islamic banking. The risk attitude affects the adoption ofIslamic banking. Adoption of Islamic banking mediates the effect of Islamic financial literacy, bankreputation, religiosity, and risk attitude on financial satisfaction. The results of the study add to the literatureand the results of empirical studies of Islamic financial management. Provide recommendations for IslamicBank policies, namely: policies to increase Islamic financial literacy, bank reputation, risk attitude, adoption ofIslamic banking, and financial satisfaction to improve the welfare and performance of the bank.